2022
DOI: 10.3390/ijms23158455
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for Activated C Kinase1B (OsRACK1B) Impairs Fertility in Rice through NADPH-Dependent H2O2 Signaling Pathway

Abstract: The scaffold protein receptor for Activated C Kinase1 (RACK1) regulates multiple aspects of plants, including seed germination, growth, environmental stress responses, and flowering. Recent studies have revealed that RACK1 is associated with NADPH-dependent reactive oxygen species (ROS) signaling in plants. ROS, as a double-edged sword, can modulate several developmental pathways in plants. Thus, the resulting physiological consequences of perturbing the RACK1 expression-induced ROS balance remain to be explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 137 publications
1
9
0
Order By: Relevance
“…In a recent study, it was demonstrated that AtRACK1, the Arabidopsis homolog of OsRACK1, participates in leaf senescence [16]. Concurrently, our research revealed that the overexpression of OsRACK1B induces ROS burst as a form of H 2 O 2 through direct interaction with the N-terminal region of OsR-bohD and affects the timing of anther dehiscence, pollen viability, and pollen cell wall integrity [11].…”
Section: Introductionsupporting
confidence: 60%
“…In a recent study, it was demonstrated that AtRACK1, the Arabidopsis homolog of OsRACK1, participates in leaf senescence [16]. Concurrently, our research revealed that the overexpression of OsRACK1B induces ROS burst as a form of H 2 O 2 through direct interaction with the N-terminal region of OsR-bohD and affects the timing of anther dehiscence, pollen viability, and pollen cell wall integrity [11].…”
Section: Introductionsupporting
confidence: 60%
“…Alternatively, Zhang et al (2013) found that the content of malondialdehyde and membrane permeability in the heat‐sensitive rice line were greater than those in the heat‐tolerant line, which was associated with a decrease in the anther dehiscence coefficient and rate of pollen germination. Recently, Rahman et al (2022) reported that hydrogen peroxide (H 2 O 2 ) negatively regulates pollen development and fertility in rice. Similarly, our data showed that HT during panicle initiation also increased the contents of reactive oxygen species (ROS), H 2 O 2 , and malondialdehyde in anthers, particularly in the heat‐sensitive rice variety LYPJ with low pollen and spikelet fertility (Hu, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rahman et al (2022) reported that hydrogen peroxide (H 2 O 2 ) negatively regulates pollen development and fertility in rice.…”
Section: Effects Of Increased Panicle Nitrogen Application On Ultrast...mentioning
confidence: 99%
“…Despite a fundamental difference in phosphorylation sites, plant RACK1s appear to be functionally similar to mammalian RACK1 [ 7 , 8 ]. In plants, RACK1 has been implicated in seed germination, root development, flowering, pollen development, and fruit ripening [ 9 , 10 , 11 ]. Mutant analysis in Arabidopsis thaliana and Oryza sativa L. plants revealed that RACK1 plays a crucial role in plants’ response to environmental stress conditions such as drought and salinity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, it was demonstrated that AtRACK1, the Arabidopsis homolog of OsRACK1, participates in leaf senescence [ 16 ]. Concurrently, our research revealed that the overexpression of OsRACK1B induces ROS burst as a form of H 2 O 2 through direct interaction with the N-terminal region of OsRbohD and affects the timing of anther dehiscence, pollen viability, and pollen cell wall integrity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%